Decisions in Labour Markets Determinants of Early Retirement in Central Europe - Pecinová, Kateřina; Pertold, Filip, 1981-; Nikolovová, Pavla, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
The financial sustainability of retirement-income systems will be seriously threatened in the future mainly due to people's exit from the labour market into early retirement at an increasingly younger age and a population with an increasing life expectation. In this thesis I investigate early retirement determinants by using a SHARE survey and three different methodologies -- a graphical comparison, a linear probability model, and multinomial logit models. Generally, two results are consistent across the models and worth highlighting, firstly there is a clear negative link between poor health and being employed, and secondly, having grandchildren translates into a higher probability of not being employed. These results imply that public policy connected to the sustainability of pension systems should have a broader context including topics like health of a population or childcare facilities.
Vedoucí práce: Filip Pertold
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses